2001
DOI: 10.1080/003655401317074653
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-related Bacteremia due to Lactobacillus rhamnosus in a Single-lung Transplant Recipient

Abstract: There is still a major debate about the pathogenicity of Lactobacillus spp. and some reports emphasize that these microorganisms are never isolated from endovascular devices. In this report we present a case of catheter-related bacteremia due to L. rhamnosus in a patient who underwent a single-lung transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
9

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 9 publications
0
8
0
9
Order By: Relevance
“…Like in our patient, the intra-abdominal abscess was possibly from bowel injury after the operation followed by translocation of intestinal microflora. Among transplant recipients, pneumonia, empyema, pyelonephritis, meningitis, catheter-associated, and surgical site infections have been reported [1,5,6,[10][11][12]. Lactobacillus bacteremia cases have almost 30 % of all-cause mortality within one month, in spite of the high clearance and low attributable mortality rate.…”
Section: Discussionmentioning
confidence: 94%
“…Like in our patient, the intra-abdominal abscess was possibly from bowel injury after the operation followed by translocation of intestinal microflora. Among transplant recipients, pneumonia, empyema, pyelonephritis, meningitis, catheter-associated, and surgical site infections have been reported [1,5,6,[10][11][12]. Lactobacillus bacteremia cases have almost 30 % of all-cause mortality within one month, in spite of the high clearance and low attributable mortality rate.…”
Section: Discussionmentioning
confidence: 94%
“…They have very low pathogenicity to humans, and are widely used as probiotics. However, they are known to cause opportunistic infections in immunosuppressed patients [8], and cases of severe infection have been reported [2][3][4][5][6][7][8][9]. Cannon et al [2] analyzed more than 200 cases of infection by Lactobacillus spp., and the most frequent causative organisms were L. rhamnosus and L. casei.…”
Section: Discussionmentioning
confidence: 99%
“…They are often used for fermentation in the food industry, and are rarely pathogenic in humans [1]. However, it has been reported that, in immunosuppressed patients or those who have undergone organ transplantation [2][3][4][5][6][7][8][9], these bacilli cause critical infections such as sepsis and infectious endocarditis. Herein, we report a case of lung abscess and pleuritis caused by Lactobacillus rhamnosus in a patient who was not immunodeficient; this is considered to be the first such case reported in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 92 human isolates (H), of which 58 are from sterile sites and 34 from commensal (mainly fecal, vaginal, and oral) human flora, were included. The human isolates were collected in hospitals or were obtained from culture collections or from authors who published clinical cases (2,3,6,9,19,21,23). The origin of the type strain of L. rhamnosus, LMG 6400, is not known.…”
Section: Methodsmentioning
confidence: 99%